Enhancing Performance: Examining the Role Played by High Performance Work System - Imran, Rabia; Majeed, Mehwish; Ayub, Abida (International Journal of Economics and Financial Issues, 2015)
The aim of this study is to examine the role of high performance work system (HPWS) in increasing performance of the employees. It further explores the mediating role played by organizational citizenship behavior (OCB) and organizational commitment in HPWS and performance relationship. A purposive sample of 330 respondents from telecom sector of Pakistan is selected for the study. The results reveal the fact that HPWS has a strong positive impact on performance. The hypothesized mediating roles of organizational commitment and organizational OCB are also partially supported. Implications and future research are also discussed. Keywords: High Performance Work System, Organizational Commitment, Organizational Citizenship Behavior, Performance JEL Classifications: L2, L25